Controversies surrounding continuous deep sedation at the end of life: the parliamentary and societal debates in France. Issue 1 (December 2016) - Raus, Kasper; Chambaere, Kenneth; Sterckx, Sigrid
Abstract Background Continuous deep sedation at the end of life is a practice that has been the topic of considerable ethical debate, for example surrounding its perceived similarity or dissimilarity with physician-assisted dying. The practice is generally considered to be legal as a form of symptom control, although this is mostly only assumed. France has passed an amendment to the Public Health Act that would grant certain terminally ill patients an explicit right to continuous deep sedation until they pass away. Such a framework would be unique in the world. Discussion In this paper we will highlight and reflect on four relevant aspects and shortcomings of the proposed bill. First, that the bill suggests that continuous deeps sedation should be considered as a sui generis practice. Second, that it requires that sedation should always be accompanied by the withholding of all artificial nutrition and hydration. In the most recently amended version of the legal proposal it is stated that life sustaining treatments are withheld unless the patient objects. Third, that the French bill would not require that the suffering for which continuous deep sedation is initiated is unbearable. Fourth, the question as to whether the proposal should be considered as a way to avoid having to decriminalise euthanasia and/or PAS or, on the contrary, as a veiled way to decriminalise these practices. Summary The French proposal to amend the Public Health Act to include a right to continuous deep sedation for some patients is a unique opportunity to clarify the legality of continuous deep sedation as an end-of-life practice. Moreover, it would recognize that the practice of continuous deep sedation raises ethical and legal issues that are different from those raised by symptom control on the one hand and assisted dying on the other hand. Nevertheless, there are still various issues of significant ethical concern in the French legislative proposal.